STRATEGI IMPLEMENTASI EKONOMI SYARIAH DI MASA PANDEMI COVID-19 - Habibi, Mohammad (Ekosiana Jurnal Ekonomi Syari ah, 2021)
Islam anticipates economic development which is considered as part of human development. Its essence is that it enables humans to control the economic environment and improve the quality of life. There are four basic teachings of Islam that deal with the philosophy of Islamic economic development: tawhîd, rubûbiyah, khalîfah and tazkiyah. In this study, using the literature review method, namely using a theory that is relevant to the research problem of Islamic Economic Development Strategies in the Covid-19 Period. The results showed that the principle of tawhid is to prevent concentrated economic power. Khalîfah The principle is to protect against environmental damage and to protect the conservation of natural resources. The principle of tazkiyah to prohibit social inequality and promote equality and justice. In line with that, it can form a continuity of development. The concept of continuity building is basically the application of the rubûbiyah principle, it is the principle of education, maintenance, and continuity of perfection, as a divine (divine) principle. Therefore, if these four principles are realized in Indonesia's development economy, the government will easily create a prosperous and just nation. Then the development strategies offered in the framework of the Islamic economic concept and system are: (1) by distributing direct cash assistance originating from zakat, donations and alms; (2) by strengthening waqf in the form of cash waqf, productive waqf, waqf linked sukuk and waqf for infrastructure; (3) through superior business capital assistance for the business sector or Micro, Small and Medium Enterprises (MSMEs); (4) through the qardhul hasan scheme; (5) increasing Islamic economic and financial literacy; (6) through the development of Islamic financial technology. Keywords: Development strategy, Islamic Economics, Pandemic Covid-19